The role of ICT use in reducing social isolation among older adults during the COVID-19 pandemic: evidence from frail and healthy older adults in Sakai City, Japan - Jianyu Huang; Richard Ssempala; Ziyan Wang (BMC Public Health)
Abstract Background Social isolation among older adults has intensified during the coronavirus disease 2019 (COVID-19) pandemic, disproportionately affecting frail older adults. This study examines the role of information and communication technology (ICT) in reducing social isolation and explores its differential effects between frail and healthy older adults. Methods This study employed a quantitative research design with cross-sectional data obtained from the “Survey on Older Adults of Sakai City” in Japan. Social isolation is measured in terms of three dimensions: loneliness, social participation, and access to social support. Ordered probit techniques were employed to estimate the effects of ICT use frequency while controlling for individual characteristics. Results Frequent ICT use, including smartphones and voice calls, was significantly associated with reduced loneliness, with frail older adults benefiting more significantly. However, ICT use had a limited impact on increasing the diversity of social participation, likely due to the substitution of in-person activities with online interactions during the pandemic. Access to social support yielded mixed results, with no consistent improvement across the entire sample. Conclusions ICT serves as a valuable tool to alleviate loneliness among older adults, especially frail older adults, but it cannot fully replace face-to-face interactions to foster diverse forms of social participation. Simplified ICT tools and tailored training programs are essential to improve accessibility for frail older adults. Future efforts should explore integrating ICT with offline activities and leveraging emerging technologies, such as video conferencing, to address social isolation more comprehensively. Trial registration Not applicable.